EFEKTIFITAS MODEL PROBLEM BASED INSTRUCTION TERHADAP KETERAMPILAN PROSES SAINS MAHASISWA PADA MATA KULIAH KONSEP SAINS - Listiani, Ivayuni (Profesi Pendidikan Dasar, 2018)
This research aims to find out the effectiveness of Problem Based Instruction model on science process skills of students in the subject of science concepts II PGRI Madiun University. This research was a quasi experiment with quantitative approach. The research design was Posttest Only Control Group Design by using model Problem Based Instruction in the experimental group and the lecture method varies in the control group. The study population was the whole second semester students Prodi PGSD PGRI Madiun University. The sampling technique used cluster random sampling, in order to obtain semeseter 2 class 2D as an experimental group and 2C as a control group. The data collection technique using a multiple choice test and essay, observation sheets, as well as their academic papers. The hypothesis testing using t-test. Normality test was performed using Kolmogorov-Smirnov test with significance of control class 0,332 and experiment class 0,538. Homogeneity test using Levene's test with significance level of 0.532. Hypothesis test results obtained a significance level of 0.00 so that the results of this study concluded that the learning model Problem Based Instruction is effective against science process skills of students in the subject of science concepts II PGRI Madiun University.